HUMAN TRAITS OF THE SUBALTERNS : A STUDY ON THE SELECT NOVELS OF AMITAV GHOSH (Forum for Linguistic Studies, 2024)
Love is the guiding spirit and force for the survival of the world. The Universal Love teaches universal brotherhood and brings the whole world under one roof of humanity. It results in a peaceful and warless world and fraternity among the nations. Mutual love leads to a good family, thereby strengthening the relationship. This paper carries out the theme of human traits of the subalterns, such as love and sacrifice, recurrent in Amitav Ghosh's novels such as “The Shadow Lines”,” The Hungry Tide,” and “Sea of Poppies."  It deals with how love leads to the sacrifice of one’s own life for the sake of others, which elevates and dignifies the love of mankind, and how love overcomes the obstacles and stumble blocks in their way.